The Thermal Stability of Lattice-Energy Minima of 5-Fluorouracil: Metadynamics as an Aid to Polymorph Prediction - Karamertzanis, P.; Raiteri, Paolo; Parrinello, M.; Leslie, M.; Price, L. (American Chemical Society, 2008)
This paper reports a novel methodology for the free-energy minimization of crystal structures exhibiting strong, anisotropic interactions due to hydrogen bonding. The geometry of the thermally expanded cell was calculated by exploiting the dependence of the free-energy derivatives with respect to cell lengths and angles on the average pressure tensor computed in short molecular dynamics simulations. All dynamic simulations were performed with an elaborate anisotropic potential based on a distributed multipole analysis of the isolated molecule charge density. Changes in structure were monitored via simulated X-ray diffraction patterns. The methodology was used to minimize the free energy at ambient conditions of a set of experimental and hypothetical 5-fluorouracil crystal structures, generated in a search for lattice-energy minima with the same model potential. Our results demonstrate that the majority (∼75%) of lattice-energy minima are thermally stable at ambient conditions, and hence, the free-energy (like the lattice-energy) surface is complex and highly undulating. Metadynamics trajectories (Laio, A.; Parrinello, M. Proc. Natl. Acad. Sci. U.S.A. 2002, 99, 12562) started from the free-energy minima only produced transitions that preserved the hydrogen-bonding motif, and thus, further developments are needed for this method to efficiently explore such free-energy surfaces. The existence of so many free-energy minima, with large barriers for the alteration of the hydrogen-bonding motif, is consistent with the range of motifs observed in crystal structures of 5-fluorouracil and other 5-substituted uracils.